CELL CYCLE ARREST ACTIVITY OF LITSEA CUBEBA LOUR: HEARTWOOD AND FRUIT EXTRACTS AGAINST T47D BREAST CANCER CELLS - Dalimunthe, Aminah; Hasibuan, Poppy Anjelisa Z; Satria, Denny (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This study was carried out to investigate cell cycle arrest activity toward T47D cells of Litsea cubeba heartwoods and fruits extract. Methods: Dry extracts were prepared from dry-grounded heartwoods and fruits by cold maceration using n-hexane, ethylacetate, and ethanol solvent. Cytotoxic activity were measured by [3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyl tetrazolium bromide] methods and interpreted with inhibitory concentration 50% (IC50) value. Cell cycle arrest was investigated by flowcytometry method. Results: IC50 values for each n-hexane, ethylacetate, and ethanol of L. cubeba heartwoods and fruits were 76.34Â±2.61; 67.52Â±2.45; 71.23Â±2.37; 75.59Â±3.24; 162.58Â±15.08; 63.70Â±2.67 Î¼g/mL, respectively. Cell cycle arrest for ethylacetate extract of heartwoods and fruits were accumulated in G0/G1 phase (56.70% and 65.56%). Conclusion: These results suggest that L. cubeba heartwoods and fruits has cell cycle arrest activity.